OPTIMALISASI DIAMETER KAWAT UNTUK KOMPONEN SENSOR SUHU RENDAH BERBASIS SUSEPTIBILITAS - HALLEYNA WIDYASARI; MOH. TOIFUR (Faktor Exacta, 2016)
Research has been carried out low-temperature sensors based magnetic susceptibility. The study was conducted in order to obtain the most appropriate wire diameter to be used as a low temperature sensor. As the sample used three solenoid with a wire diameter of 0.10 mm; 0.15 mm; and 0.20 mm. Experiments performed using the room temperature was varied from 157K until 253K. Data collection was performed on the multimaster current, the magnetic field induced by the gaussmeter, medium temperature with a digital thermocouple. Medium magnetic susceptibility values obtained by linear regression of data electric current and magnetic induction. Based on the analysis of the data it can be concluded solenoid with a wire diameter of 0.15 mm is most suitable solenoid is used as a temperature sensor cold. This sensor has a degree of linearity better and more sensitive than other sensors. Equation-temperature circuit followed by I is the current and T the temperature of the medium.